Self-retranslation as a rite of passage : Rosario Ferré's English version of "La muñeca menor" - Spoturno, María Laura (2018)
Este artículo aborda un caso de auto-retraducción que implica a dos figuras destacadas del campo literario y del campo de la traducción en Latinoamérica y Estados Unidos: la escritora puertorriqueña Rosario Ferré y el traductor estadounidense Gregory Rabassa. Publicada originalmente en 1972, "La muñeca menor" es uno de los cuentos más renombrados de Ferré. La traducción inicial de Rabassa, publicada en 1980 con el título de "The Youngest Doll" fue prontamente reemplazada por una segunda versión del texto, cuya autoría corresponde a la propia autora y a la investigadora feminista Diana Vélez (1986). El estudio de "La muñeca menor" y de sus versiones en inglés retoma uno de los textos que Ferré auto-(re)tradujo y pondera el impacto de la auto-retraducción en la formación de su identidad como escritora. El análisis de los textos se centra en los siguientes interrogantes: (1) ¿En qué medida la retraducción de Ferré se constituye en una nueva versión del cuento o es, en realidad, una revisión del trabajo de Rabassa? En otras palabras, ¿el texto retraducido evidencia una interpretación diferente del texto fuente? ¿Las versiones estudiadas despliegan mecanismos discursivos y literarios diversos? (2) ¿Cuál es la reinscripción socio-cultural, literaria e institucional del texto objeto de estudio? ¿Qué factores han contribuido a la aparición de esta segunda versión en inglés? (3) ¿De qué modo se relacionan estas versiones con campos culturales y literarios específicos?
This paper explores a case of self-retranslation involving two prominent figures of the literary and translation fields in Latin America and the United States: Puerto Rican writer Rosario Ferré and US American translator Gregory Rabassa. Originally published in Spanish in 1972, "La muñeca menor" is one of Ferré's best-known and popular stories. Rabassa's initial translation of the story, published in 1980 as "The Youngest Doll," was soon overshadowed by the second version of the text, which was penned by the author herself in collaboration with feminist scholar Diana Vélez (1986). The study of "La muñeca menor" and its companion English versions revisits the first piece Ferré ever self- (re)translated while it assesses the impact of self-retranslation in shaping her identity as a writer. While discussing various aspects of the texts, the analysis focuses on these questions: (1) To what extent does Ferré's retranslation make for a new version of the story or is, rather, a revision of Rabassa's work? That is, does the retranslated version evidence a competing interpretation of the source text? Do these versions display different discursive and literary mechanisms? (2) What is the socio-cultural, literary and institutional re-inscription of the text in the versions under study? What factors have led to this second English version of the story? (3) How do these versions relate to specific cultural, literary and translation fields?
Cet article présente un cas d'auto-retraduction concernant deux personnalités remarquables du champ littéraire et de celui de la traduction en Amérique Latine et aux Etats-Unis : l'écrivaine portoricaine Rosario Ferré et le traducteur américain Gregory Rabassa. Publié d'abord en 1972, "La muñeca menor" constitue l'un des contes les plus renommés de Ferré. La première traduction de Rabassa, parue en 1980 et intitulée"The Youngest Doll" a été bientôt remplacée par une deuxième version du texte, de la main de la même auteure et de la chercheuse féministe Diana Vélez (1986). L'étude de"La muñeca menor" et de ses versions en anglais reprend un des textes auto-(re)traduit par Ferré et examine l'impact de l'auto-retraduction sur la formation de son identité en tant qu'écrivaine. L'analyse des textes se centre sur les questions suivantes. (1) Dans quelle mesure la retraduction de Ferré constitue-t-elle une nouvelle version du conte ou s'agit-il en réalité d'une révision du travail de Rabassa ? En d'autres mots, le texte retraduit met-il en évidence une interprétation différente du texte source ? Les versions étudiées déploient-elles des mécanismes discursifs et littéraires divers ? (2) Quelle est la réinscription socio-culturelle, littéraire et institutionnelle du texte objet d'étude ? Quels sont les facteurs qui ont contribué à l'apparition de cette deuxième version en anglais ? (3) De quelle manière ces versions se mettent-elles en relation avec des champs culturels et littéraires spécifiques ?
The research presented in this paper has been supported by the project "Escrituras de minorías, (auto) traducción y ethos" (UNLP, H/825, 2017-2020) and the National Scientific and Technical Research Council (CONICET, Argentina). An earlier version of the paper was presented at the III Retranslation in Context Conference at Ghent University in 2017.
Keywords: Auto-retraducción; Rosario Ferré; "La muñeca menor"; Ethos feminista; Autora latina de Estados Unidos; Rosario Ferré; Self-retranslation; UD latina writer; "La muñeca menor"; Feminist ethos; Auto-retraduction; Rosario Ferré; "La muñeca menor"; Ethos féministe; Auteure latine des E0tats-Unis^lfr